Resource‐enhancing global changes drive a whole‐ecosystem shift to faster cycling but decrease diversity. Issue 12 (1st October 2020) - Eskelinen, Anu; Gravuer, Kelly; Harpole, W Stanley; Harrison, Susan; Virtanen, Risto; Hautier, Yann
Abstract: Many global changes take the form of resource enhancements that have potential to transform multiple aspects of ecosystems from slower to faster cycling, including a suite of both above‐ and belowground variables. We developed a novel analytic approach to measure integrated ecosystem responses to resource‐enhancing global changes, and how such whole ecosystem slow‐to‐fast transitions are linked to diversity and exotic invasions in real‐world ecosystems. We asked how 5‐yr experimental rainfall and nutrient enhancements in a natural grassland system affected 16 ecosystem functions, pools, and stoichiometry variables considered to indicate slow vs. fast cycling. We combined these metrics into a novel index we termed "slow‐fast multifunctionality" and assessed its relationship to plant community diversity and exotic plant dominance. Nutrient and rainfall addition interacted to affect average slow‐fast multifunctionality. Nutrient addition alone pushed the system toward faster cycling, but this effect weakened with the joint addition of rainfall and nutrients. Variables associated with soil nutrient pools and cycling most strongly contributed to this antagonistic interaction. Nutrient and water addition together, respectively, had additive or synergistic effects on plant trait composition and productivity, demonstrating divergence of above‐ and belowground ecosystem responses. Our novel metric of faster cycling was strongly associated with decreased plant species richness and increased exotic species dominance. These results demonstrate the breadth of interacting community and ecosystem changes that ensue when resource limitation is relaxed.